2008
DOI: 10.1068/a41271
|View full text |Cite
|
Sign up to set email alerts
|

When Tony Met Bobby

Abstract: When Tony met BobbyIn June 1999 Wal-Mart intervened spectacularly in an agreed merger between Asda and Kingfisher by paying »6.7 billion to take over Asda outright. Reactions ranged dramatically (Whysall, 2001); this was the death-knell of British retailing or the redemption of British consumers. Whatever the view, Wal-Mart buying a major retailer such as Asda, and in such a significant European market, was a landmark in the globalisation of retailing.One issue around this takeover attracted considerable specu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Within retailing for example, this agency at various spatial scales is evident in responding to (and affecting) regulation at a national level in host markets as part of international expansion (Sparks, 2008), or equally appealing against local decisions within specific local geographies in domestic markets (Guy and Bennison, 2007). This places an emphasis on the availability and usage of resources by corporate actors as well as by state level agents, whether this is in the form of material resources, knowledge, power or social capital (Bathelt and Glückler, 2005).…”
Section: The Relational Nature Of Regulatory Implementation: Resourcementioning
confidence: 99%
“…Within retailing for example, this agency at various spatial scales is evident in responding to (and affecting) regulation at a national level in host markets as part of international expansion (Sparks, 2008), or equally appealing against local decisions within specific local geographies in domestic markets (Guy and Bennison, 2007). This places an emphasis on the availability and usage of resources by corporate actors as well as by state level agents, whether this is in the form of material resources, knowledge, power or social capital (Bathelt and Glückler, 2005).…”
Section: The Relational Nature Of Regulatory Implementation: Resourcementioning
confidence: 99%
“…We confirmed that the store format with the greatest impact on traditional markets and their SME traders is the large discount store rather than the supermarket. Importantly, too, rivalry is keenest from re-energised local incumbents rather than strictly from TNCs -meaning that Arguably, many of the regulatory laws which were legislated in developed countries in the 1980s and the 1990s have declined recently: sometimes with lobbying from transnational retailers (Sparks 2008). In some developed countries, local governments still use regulatory laws, but fewer developed countries see their central government driving forward regulations on large distribution enterprises.…”
Section: Discussionmentioning
confidence: 99%
“…The role of government is more difficult to predict. As revealed by Sparks () and predicted by Clegg (), powerful global retailers do not just write letters of protest. They gain access to the highest levels of government specifically in the hope of having laws changed.…”
Section: Theoretical Underpinnings and Methodologymentioning
confidence: 99%